Pengaruh Ukuran Perusahaan dan Profitabilitas terhadap Nilai Perusahaan Dengan Kepemilikan Manajerial sebagai Variabel Moderasi - Abimanyu Nur Indra; Hadi Pramono; Iwan Fakhrudin; Selamet Eko Budi Santoso (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
Company value reflects business performance and prospects in the eyes of investors, but not all companies are able to maintain it amid market dynamics. Internal factors such as company size and profitability, as well as the role of managerial ownership, are key in determining how much the value of a company can grow and be sustainable. The primary objective of this investigation is to demonstrate how the dimensions of a company and its profitability can impact the overall value of a business, with managerial ownership playing a significant role. The research focuses on companies within the non-cyclical consumer sector listed on the Indonesia Stock Exchange between 2021 and 2023. Through the researcher's specified criteria, a sample consisting of 83 data points was selected for analysis. According to the research results, the company's value is greatly impacted by its profitability, rather than its size. Furthermore, when testing with MRA interaction, it was found that managerial ownership can enhance the link between company size and value, but it does not have the same effect on the relationship between profitability and value.